Heterotopic pancreas causing duodenal obstruction in a patient previously treated for choledochal cyst - Vidyanand P Deshpande; B V Raghunath; Yogesh K Sarin; Shalini Sinha (Wolters Kluwer Medknow Publications, 2012)
A 9-year-old boy presented with duodenal pancreatic rest causing obstruction and required surgical intervention. He had been treated at the age of 4 months for a choledochal cyst. Both choledochal cyst and heterotopic pancreas are entities that are commonly encountered in children, but the incidental presence of both the entities in the same child, albeit presenting metachronously, is extremely rare.